Implementasi Peraturan Daerah tentang Bangunan Gedung dan Surat Keputusan Bersama 2 Menteri terhadap Pembangunan Rumah Ibadah Non-Muslim di Kabupaten Jeneponto - Rifat, Andi Muh. Iqrah; Marilang (Universitas Islam Negeri Alauddin Makassar, 2023)
Implementation of Regional Regulation No. 3 of 2014 concerning Buildings and the Joint Decree (SKB) of 2 Ministers on the Construction of Non-Muslim Houses of Worship by describing some of the results of the research while on site. This research in Kec. Binamu Kab. Jeneponto, field research with an empirical approach which is one of the research methods that uses descriptive data in the form of words from related parties which is then supported by various literary sources from books, journals, articles, theses and other written works. The results obtained by the author in this study Implementation of Ministerial Decree No. 2, 8 and 9 of 2006 and Regional Regulation No. 3 of 2014 Regarding Buildings, everything has been clearly regulated and has been running properly. Without exception the construction of houses of worship which often triggers conflicts to this day. Even though it is clear that the provisions in the above rules do not distinguish between the construction of Muslim and non-Muslim houses of worship. Because the administrative requirements are the same.